Effects of dietary crude protein level and N-carbamylglutamate supplementation on nutrient digestibility and digestive enzyme activity of jejunum in growing pigs - Wang, Yuming (J Anim Sci, 2020)
Three experiments were conducted to investigate the effects of dietary crude protein (CP) level and N-carbamylglutamate (NCG) supplementation on apparent total tract digestibility (ATTD) and ileal digestibility of nutrients and digestive enzyme activity of jejunum in growing pigs. In experiment 1, 10 Duroc × Landrace × Yorkshire barrows (initial BW: 48.7 kg) were allotted to a three-period switchback design with five experimental diets and two replicate pigs per diet in each period. Diets were categorized as high CP (HP, 18% CP), moderate low CP (MLP, 15% CP), very low CP (VLP, 12% CP), and MLP and VLP with 0.1% NCG supplementation. Feces and urine were collected from day 6 to day 11 after a 5-d adaptation period. The DE, ME, and ATTD of GE, OM, CP, NDF, ADF, and P decreased (P < 0.01) with a reduction of dietary CP, but no effect of dietary treatments on pig daily N retention was detected. The NCG supplementation increased (P < 0.01) DE and ATTD of ADF of the VLP diet. In experiment 2, 10 jejunal-cannulated Duroc × Landrace × Yorkshire barrows (initial BW: 44.5 kg) were fed five diets for three periods as experiment 1. Jejunal fluid was collected on days 6 and 8 after a 5-d adaptation period. The digestive enzymes activity was not affected by dietary CP level, except for α-amylase, for which there was a decrease (P < 0.01) in pigs fed VLP diets compared to HP and MLP diets. In experiment 3, 12 ileal-cannulated Duroc × Landrace × Yorkshire barrows (initial BW: 46.7 kg) were allotted to a three-period switchback design with six diets and two replicate pigs per diet in each period. The six experimental diets consisted of five experimental diets as experiment 1 and one N-free diet. Ileal digesta was collected from day 6 to day 8 after a 5-d adaptation period. Results indicated that apparent ileal digestibility (AID) of CP and P and ileal digestibility of Arg, His, Ile, Leu, Phe, and all dispensable AA, except Pro, decreased (P < 0.01) in pigs fed VLP diet compared to HP and MLP diets, but AID of GE, OM, EE, NDF, and ADF were not affected. The supplementation of NCG in the VLP diet increased (P < 0.01) the AID of CP and ileal digestibility of Arg, His, Leu, Phe, Val, Ser, and Tyr. In conclusion, reducing dietary CP level decreased nutrient digestibility, but improved the efficiency of dietary N utilization and reduced N emission. Moderate reduction of dietary CP level had a minimal effect on nutrient digestibility and digestive enzyme activity. Additionally, NCG supplementation plays a beneficial effect on nutrient digestion only if the dietary CP level is extremely lowered.